2020
DOI: 10.1101/2020.05.07.083667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Born to be young: prenatal thyroid hormones increase early-life telomere length

Abstract: 43 44 Character count: 9400 45 Reference count: 15 46 47 Keywords 48 Aging, mitochondria, telomere length, bird, fetal programming. Abstract 51 Prenatal environmental conditions can have lifelong consequences on health and aging. The 52 underlying mechanisms remain nonetheless little understood. Thyroid hormones (THs) are important 53 regulators of embryogenesis transferred from the mother to the embryo. In an avian model, we 54 manipulated embryo exposure to maternal THs through egg injection and investigated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In turn, the lack of treatment effects on adult oxidative status may suggest no organisational effects of prenatal THs on adult metabolism. Two recent studies in altricial species also found no influence of yolk THs on nestling oxidative stress ( Hsu et al, 2019 ; Sarraude et al, 2020 ), yet telomere length, a biomarker of aging was affected ( Stier et al, 2020 ). Our study shows for the first time that prenatal THs have no influence on adult oxidative stress either.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the lack of treatment effects on adult oxidative status may suggest no organisational effects of prenatal THs on adult metabolism. Two recent studies in altricial species also found no influence of yolk THs on nestling oxidative stress ( Hsu et al, 2019 ; Sarraude et al, 2020 ), yet telomere length, a biomarker of aging was affected ( Stier et al, 2020 ). Our study shows for the first time that prenatal THs have no influence on adult oxidative stress either.…”
Section: Discussionmentioning
confidence: 99%